Be my guest! Challenges and practical solutions of undertaking interviews with children in the home setting. (December 2015) - Coad, Jane; Gibson, Faith; Horstman, Maire; Milnes, Linda; Randall, Duncan; Carter, Bernie
This article aims to share critical debate on undertaking interviews with children in the home setting and draws on the authors' extensive research fieldwork. The article focuses on three key processes: planning entry to the child's home, conducting the interviews and exiting the field. In planning entry, we include children's engagement and issues of researcher gender. In conducting the interviews, we consider issues such as the balance of power, the importance of building a rapport, the voluntary nature of consent and the need for a flexible interview structure. Finally, we address exiting from the child's home with sensitivity at the end of the interview and/or research study. Undertaking research in the child's home provides a known and familiar territory for the child, but it means that the researcher faces a number of challenges that require solutions whilst they are a guest in a child's home.